2021
DOI: 10.1109/access.2021.3064000
|View full text |Cite
|
Sign up to set email alerts
|

Active Learning for Biomedical Text Classification Based on Automatically Generated Regular Expressions

Abstract: Biomedical text classification algorithms, which currently support clinical decision-making processes, call for expensive training texts due to the low availability of labeled corpus and the cost of manual annotation by specialized professionals. The active learning (AL) approach to classification heavily lessens such cost by reducing the number of labeled documents required to achieve specified performance. This article introduces a query strategy and a stopping criterion that transform CREGEX, a regular-expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 39 publications
(51 reference statements)
0
5
0
1
Order By: Relevance
“…Flores et al [19] present extensive comparisons of alternative models, such as active learning, SVM, Naïve Bayes, and a BERT classifier applied to biomedical datasets. They found that the active learning approach reduced the number of training examples necessary for achieving the same performance of the other classifiers.…”
Section: Related Workmentioning
confidence: 99%
“…Flores et al [19] present extensive comparisons of alternative models, such as active learning, SVM, Naïve Bayes, and a BERT classifier applied to biomedical datasets. They found that the active learning approach reduced the number of training examples necessary for achieving the same performance of the other classifiers.…”
Section: Related Workmentioning
confidence: 99%
“…The SMFCNN obtained high accuracy, demonstrating its capability to classify long text documents in Urdu. Flores, Figueroa & Pezoa (2021) developed a query strategy and stopping criterion that transformed Classifier Regular Expression (CREGEX) in an active learning (AL) biomedical text classifier. As a result, the AL was permitted to decrease the number of training examples required for a similar performance in every dataset compared to passive learning (PL).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Existen varios trabajos enfocados en el uso secundario de datos médicos y clasificación de textos desarrollados por investigadores de la Universidad de Concepción 43 , 44 , 45 . En esta propuesta se emplearon textos clínicos en español, provenientes del Hospital Clínico Regional Dr. Guillermo Grant Benavente de Concepción, para identificar y extraer información sobre el estado de tabaquismo de los pacientes, mediante técnicas de PLN y minería textual 46 , junto con información sobre medidas de peso corporal y comorbilidades 47 .…”
Section: Otros Sistemas De Pln Clínico Desarrollados En Chileunclassified